Stability of the Colloidal Chromic Radiophosphate (32p) to the Isotopic Exchange - Anghileri, Leopoldo José; Marqués, Roberto Oscar (1966)
Fil: Anghileri, Leopoldo José Comisión Nacional de Energía Atómica; Argentina